Association Between a 20‐Year Cardiovascular Disease Risk Score Based on Modifiable Lifestyles and Total and Cause‐Specific Mortality Among US Men and Women. Issue 21 (6th November 2018) - Sotos‐Prieto, Mercedes; Mattei, Josiemer; Cook, Nancy R.; Hu, Frank B.; Willett, Walter C.; Chiuve, Stephanie E.; Rimm, Eric B.; Sesso, Howard D.
Abstract : Background: The previously validated Healthy Heart Score effectively predicted the 20‐year risk of cardiovascular disease (CVD). We examine whether the Healthy Heart Score may extend to an association with total and cause‐specific mortality. Methods and results: The prospective cohort study investigated 58 319 women (mean age 50.2 years) in the Nurses' Health Study (1984–2010) and 29 854 in men (mean age 52.7 years) in the Health Professionals' Follow‐up Study (1986–2010) free of cancer and CVD at baseline. The Healthy Heart Score included baseline current smoking; high body mass index; low physical activity; no or excessive alcohol intake; low intake of fruits and vegetables, cereal fiber, or nuts; and high intake of sugar‐sweetened beverages or red/processed meats. There were 19 122 total deaths. Compared with participants in the first quintile of the Healthy Heart Score (lowest CVD risk), participants in the fifth quintile (highest CVD risk) had a pooled hazard ratio of 2.26 (95% confidence interval [CI], 1.53–3.33) for total mortality; 2.85 (95 % CI, 1.92–4.23) for CVD mortality, and 2.14 (95% CI, 1.56–2.95) for cancer mortality. Participants in the fifth versus the first quintile also had significantly greater risk of death due to coronary heart disease (3.37; 95% CI, 2.16–5.25), stroke (1.75; 95% CI, 1.02–2.99), lung cancer (6.04; 95% CI, 2.78–13.13), breast cancer (1.45; 95% CI, 1.14–1.86), and colon cancer (1.51; 95% CI, 1.18–1.93). Conclusions: The Healthy Heart Score, composed of 9 self‐reported, modifiable lifestyle predictors of CVD, is a potentially useful tool for the counseling of healthy lifestyles that was strongly associated with greater risk of all‐cause, CVD, and cancer mortality.